Review article: the assessment and management of chronic severe gastrointestinal dysmotility in adults. Issue 10 (19th September 2013) - Paine, P.; McLaughlin, J.; Lal, S.
Summary Background The characterisation and management of chronic severe gastrointestinal (GI) dysmotility are challenging. It may cause intestinal failure requiring home parenteral nutrition (HPN). Aims To review the presentation, aetiology, characterisation, management and outcome of chronic severe GI dysmotility, and to suggest a pragmatic management algorithm. Methods PubMed search was performed up to December 2012 using appropriate search terms, restricted to human articles and reviewed for relevance. Segmental dysmotility, acute ileus, functional syndromes and non‐English articles were excluded. Evidence and recommendations were evaluated using the GRADE system. Results In total, 721 relevant articles were reviewed. A coherent and definitive picture is hampered by overlapping classification systems using multi‐modal characterisation methods, subject to pitfalls and some requiring further validation. The literature is confined to case series with no randomised trials. Fewer than 20% undergo full thickness jejunal biopsy, which are otherwise labelled idiopathic. However, in studies with up to 80% biopsy rates, neuromuscular abnormalities may be found in 90%. Between 14% and 50% will require HPN, comprising 8–14% of all HPN patients, of which 2/3 are primary/idiopathic and 1/3 secondary, with scleroderma being the leading secondary cause. Ten‐year mortality ranges from 13% to 35% and is worst in elderly scleroderma patients. Management includes limited treatments for secondary causes, prokinetics, symptom palliation, psychological support, nutrition, hydration and judicious surgery. Conclusions Severe dysmotility often remains idiopathic. It is rarely possible to alter disease trajectory; consequently, prognosis may be poor. Multi‐disciplinary teams in a specialist setting can improve outcomes. Graded recommendations are enumerated and a pragmatic algorithm is suggested.